The space of the Holy Land in the 16th-century descriptions of Polish pilgrims - Ossowska-Kulińska, Katarzyna (Lodz University Press, 2022)
The Holy Land is recognized due to its unique location for the events described in The Bible and its depicted this way since the Second Century. You cannot find any other region that holds so many of geographical, historical, and literary masterpiecies. One of the most interesting resources of presenting this region is the peregrinations which serve as the written memory of the pilgrimages to the Holy Land. The diaries, summaries of events, and guides for the pilgrims count for the majority of the Western European and Late Middle Ages Pilgrimages. This genre includes four unique peregrinations of the Holy Land written by the Polish authors, which are as follows: Terrae sancte et urbis Hierusalem descriptio fratris Anzelmi ordinis Minorum de observantia by Anzelm Pollak, Jan Twardowski’s itenary, Jan Gorynski’s diary and the description of the journey to the Holy Land Syria and Egypt by Mikolaj Krzysztof "the Orphan" Radziwil. They were published only in XVI century, much later than the Italian or German masterpieces. Does the question arise if those four literary works differ from the Western European Pilgrimages to Palestine? What was the most interesting part of these pilgrimages and how The Holy Land was presented? What is the uniqueness of the Polish masterpieces describing the exploration of the Holy Places? Is their main focus on the religious aspect of Palestine or maybe they also present the oriental atmosphere of this place? In this book, you can find the answers to the above questions but not limited to those. I believe you might be interested in the pilgrimages to the Holy Land by Polish pilgrims who also discovered the Middle East’s culture and Nature.